Polyurethane foam disk passive sampler derived air concentrations of persistent organic pollutants in an agricultural region with hot climate - Güven, Emine Can; Gedik, Kadir; Kurt Karakuş, Perihan Binnur (My University, 2019)
Polyurethane foam (PUF) disks passive air samplers were deployed in an agricultural region with hot climate to determine atmospheric concentrations of 22 organochlorine pesticides (OCPs) and 15 polychlorinated biphenyls (PCBs). Sampling rates (2.39–15.9m3.day?1) increased with rising ambient air temperatures. Total OCP and PCB concentrations were 0.884–97.0 pg.m?3 and nd-213 pg.m?3, respectively. The most prominent OCPs in the samples were hexachlorocyclohexane (HCH) isomers, chlordane compounds, dichlorodiphenyltrichloroethane (DDT) derivatives, and endosulfan isomers. The isomer ratios of DDT and Chlordane in the samples indicated older usage while endosulfan ratios showed recent input of technical endosulfan in the region. Total PCB levels were dominated by low chlorinated congeners. The contaminant levels in air samples were mainly lower or similar by comparison to other studies conducted at agricultural regions worldwide. Although the production and use of these chemicals have been banned, results of this study show that some of the chemicals could still be found in agricultural areas. Presence of these chemicals in environmental samples may be result of the degradation of formerly used chemicals, atmospheric transport or illegal use of banned chemicals.
Keywords: [No Keywords]